Defining, Understanding and Promoting Cultural Diversity Through the Human Library Program - Yap, Joseph M.; Labangon, Donna; Cajes, May (Department of Information Management, University of the Punjab, Lahore, 2017)
This paper will provide the role of libraries in promoting dialogues to reduce discrimination, share how libraries document human library sessions as a form of oral history, and provide information on the “effect” of human library sessions to readers. This case study documents the human library program as an alternative source of information which promotes cultural diversity to improve many facets of literacies which include media and information literacy. Human library aims to lessen our prejudices and makes us more tolerant individuals. In order to achieve cultural equality and social inclusivity, DLSU Libraries continues to offer human library sessions to form critical thinkers, lifelong learners and catalysts for social transformation. Most readers thought that the most important learning experience they gained while reading the books was to accept and understand each one of us as unique individuals. The human library program encourages people to be more tolerant and embolden acceptance.
Keywords: human library